The Characteristics of Chronic Rhinosinusitis at Wangaya Regional Hospital Denpasar Period January-December 2022 - Kiantimi, Ni Putu Omasih; Wartawan, I Nengah (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Chronic rhinosinusitis is inflammation that affects the nose and paranasal sinuses accompanied by two or more symptoms, one of which is blockage or obstruction in the nose and nasal mucus that flows posteriorly or anteriorly which can be accompanied by additional symptoms in the form of pain or pressure on the face and reduced olfactory sensitivity or loss of smell when symptoms more than 12 weeks. Chronic rhinosinusitis has a greater impact on reducing quality of life and huge burden of health costs than acute rhinosinusitis. This research was retrospective descriptive uses secondary data from medical records January-December 2022 Otorhinolaryngology Department of Wangaya Regional Hospital Denpasar. The sampling technique used was total sampling. Data collected included gender, age, occupation, main complaint, comorbidities, number of sinus involvement, location of sinuses, therapy. The data obtained were analyzed univariately using SPSS software version 23.0 and presented in the form of tables and narratives. From the research, it was obtained that the gender was mostly female 51.2%, average age of 38.05 ± 14.26 years with the highest age group is 46-60 years old, mostly private employees 48.8%. The most common main complaint was a blocked nose 48.8%. The highest comorbid was septum deviation 14%. The majority of sinuses involved were single rhinosinusitis 67%. The highest location in the maxillary sinus 69.8%. The majority of therapy was medication 58.1%. Most cases were found in female gender, average age 38.05 ± 14.26 year age group is 46-60 years old, private employees, main complaint was blocked nose, comorbidities with deviated septum, single rhinosinusitis, the highest location in the maxillary sinus, medicamentosa therapy. Keywords: Characteristics, Patients, Chronic Rhinosinusitis